Identification of Secondary Metabolites of Onion Peels Extract (Allium cepa L.) of Various Solvent: Identifikasi Senyawa metabolit Sekunder Ekstrak Kulit Bawang Merah (Allium cepa L.) dari Berbagai Macam Pelarut - Mercyska Suryandari; Galuh Gondo Kusumo (Journal Pharmasci (Journal of Pharmacy and Science), 2022)
Onion peels (Allium cepa L.) is often disposed of without being used and ends up as waste in markets that can pollute the environment. Onion peels can potentially be developed for treatment as an anti-cancer because of its phytochemical compounds. Previous studies have shown that secondary metabolites found in onion peels using different solvents produce different secondary metabolites. So the purpose of this study was to find out the secondary metabolite compounds from onion peels extract (Allium cepa L.) qualitatively when extracted using 5 different solvents. This research was conducted using a phytochemical screening method on the onion peels extract (Allium cepa L.). n-Hexane, Ethyl Acetate, Acetone, Ethanol 96%, and Chloroform were used in the maceration extraction method separately. The results showed that the yield value was 0.96%; 2.66%; 3.90%; 4.80%; 1.62%. The results showed that acetone, ethanol, and chloroform extracts of onion peels extract (Allium cepa L.) contained alkaloids, flavonoids, saponins, steroids, terpenoids, and tannins. Meanwhile, the ethyl acetate extract of onion peels contains alkaloids, flavonoids, steroids, terpenoids, and tannins. Lastly, the n-hexane extract of the onion peels only contains steroids and terpenoids. So it can be concluded that secondary metabolites in onion peels extract contain alkaloids, flavonoids, saponins, steroids, terpenoids, and tannins.